Pharmacokinetic Profile of Spectrum Reduced Nicotine Cigarettes. Issue 2 (20th March 2019) - Kamens, Helen M; Silva, Constanza P; Nye, Russell T; Miller, Carley N; Singh, Nayantara; Sipko, Joseph; Trushin, Neil; Sun, Dongxiao; Branstetter, Steven A; Muscat, Joshua E; Richie, John P; Foulds, Jonathan
Abstract: Introduction: Spectrum research cigarettes have been developed with varying nicotine content for use in studies evaluating the effects of a regulatory policy reducing the permissible nicotine content in cigarettes. This study aimed to characterize the nicotine pharmacokinetic profile of Spectrum cigarettes. Methods: Twelve daily smokers attended four sessions and had blood nicotine, exhaled carbon monoxide, and subjective effects measured before and after smoking either a single cigarette of their preferred brand or high (10.9 mg/cigarette), medium (3.2 mg/cigarette), or low (0.2 mg/cigarette) nicotine content Spectrum research cigarettes, in a double-blind design with order counterbalanced. Results: The boost in blood nicotine concentration was dose-dependent, with a boost of 0.3, 3.9, and 17.3 ng/mL for low-, medium-, and high-nicotine content Spectrum cigarettes. The high dose Spectrum had a similar nicotine boost to the "preferred brand" cigarettes (19 ng/mL). Subjects took longer puffs on the low nicotine cigarettes, but smoked these cigarettes faster than other cigarette types. High nicotine Spectrum cigarettes reduced the urge to smoke more than other cigarette types. Conclusions: This study shows that Spectrum research cigarettes produce blood nicotine absorption in a dose-dependent manner, and therefore, are appropriate for use in studies of nicotine reduction in cigarettes. Implications: This is the first study to determine the pharmacokinetic profile of Spectrum reduced nicotine content research cigarettes following an overnight abstinence. These data could provide evidence to regulatory agencies about the effects of reduced nicotine cigarettes when considering regulations on tobacco reduction.